Assessment of Dental Nutrition Knowledge among Nutrition/ Dietetics Students - SALIL BAPAT (Journal of Clinical and Diagnostic Research, 2016)
Introduction: Diet and nutrition plays an important role in signifying the health of an individual. Oral health is the most important aspect of the body when it comes to food intake and its health benefits. It is important for the nutrition/dietetics students to be aware of the health modalities related to oral aspect. Aim: The aim of the present study was to assess knowledge towards the effect of diet and nutrition on oral health among nutrition/dietetics students of Udaipur city, Rajasthan, India. Materials and Methods: A descriptive cross-sectional study was conducted among all the nutrition and dietetics students of Udaipur city. A self-administered, pretested 14 item questionnaire was given to 180 students to assess their knowledge about dietary factors related to caries, anticariogenic foods, frequency and duration of sugar intake etc. One-way analysis of variance and independent sample t-test were utilized for statistical analysis. Confidence level and level of significance were set at 95% and 5%, respectively. Results: The mean score for knowledge was 28.92±1.72. Mean knowledge scores for III, II and I year students were 29.91±1.94, 29.56±1.27 and 27.30±1.66 respectively. When post-hoc Bonferroni test was applied, mean knowledge score was found to be at a higher end among III year as compared to I year (p=0.03) students. Conclusion: This study highlights about low dental nutrition knowledge among nutrition/dietetics students. Health professionals should have more information outside their immediate fields. Inter-professional team members should work in collaboration with each other to improve patient outcomes.